2022
DOI: 10.1155/2022/8437548
|View full text |Cite|
|
Sign up to set email alerts
|

Deep Learning of Subject Context in Ideological and Political Class Based on Recursive Neural Network

Abstract: Ideological and political education is the most important way to cultivate students’ humanistic qualities, which can directly determine the development of other qualities. However, at present, the direction of ideological and political innovation in higher vocational colleges is vague. In response to this problem, this study proposes a model based on HS-EEMD-RNN. First, the ensemble empirical mode decomposition (EEMD) method is used to decompose the measured values, and then the recurrent neural network (RNN) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…In addition, artificial intelligence is effective in enhancing teaching efficiency and effectiveness. It is believed to overcome the challenges of accuracy and cost [ 69 ]. Information technology can also be integrated with the teaching of ideological and political courses to develop a teaching quality evaluation system based on the fusion of data from multiple sources [ 70 ].…”
Section: Resultsmentioning
confidence: 99%
“…In addition, artificial intelligence is effective in enhancing teaching efficiency and effectiveness. It is believed to overcome the challenges of accuracy and cost [ 69 ]. Information technology can also be integrated with the teaching of ideological and political courses to develop a teaching quality evaluation system based on the fusion of data from multiple sources [ 70 ].…”
Section: Resultsmentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
“…Tis article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. Tis investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%